A feasibility study of Augmented Reality Intervention for Safety Education for farm parents and children - Namkoong, Kang; Leach, John; Chen, Junhan; Zhang, Jiawen; Weichelt, Bryan (Frontiers in Public Health, 2023)
Agriculture is one of the most dangerous occupations with high rates of accidents and fatalities in the western world (Shortall et al., 2019) and in the United States (CDC, 2014; Tingle et al., 2018). Especially, agriculture is more dangerous for children than any other demographic, having more younger worker deaths than any other industry and a much higher proportion of youth worker deaths compared to adult workers (Mardis & Pratt, 2003). Augmented Reality (AR) technology has a great potential to enhance the effectiveness of safety education due to its high levels of system-user interactivity and media enjoyment. AR technology allows computer-generated or extracted real-world sensory information (e.g., sound, video, or graphics) to be overlaid on a physical environment directly or indirectly in real time (Azuma, 1997; Lee, 2012; Zhou et al., 2008). Thus, this study aims to: (1) develop Augmented Reality Intervention for Safety Education (ARISE), (2) examine feasibility of ARISE, and (3) evaluate the potential of ARISE as an effective agricultural safety education program for farm parents and children. ARISE is an AR 3D simulator that presents farm accident situations with immersive media technology. To test the feasibility of ARISE, we conducted semi-structured in-depth interviews with ten parent-child dyads on November 9th and 16th in 2019 at an extension office located in Maryland. Eligible participants were farmers who owned and operated a family farm(s) with their child or children of age 5 to 11. The interviews were then transcribed and analyzed following conventional content analysis method (Hsieh & Shannon, 2005). Two main themes, acceptability and implementation, emerged to help us understand how an immersive experience through ARISE can play an impactful role in enhancing agricultural safety. The feasibility of ARISE sheds light on the potential of the AR intervention for an innovative safety education program. ARISE can contribute to the prevention of agriculture-related injuries and fatalities by providing farm parents and children with a user-friendly platform and vivid second-hand experience of incidents that frequently occur in farms.